If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(5 + -7n) = 72 (5 * 6 + -7n * 6) = 72 (30 + -42n) = 72 Solving 30 + -42n = 72 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-30' to each side of the equation. 30 + -30 + -42n = 72 + -30 Combine like terms: 30 + -30 = 0 0 + -42n = 72 + -30 -42n = 72 + -30 Combine like terms: 72 + -30 = 42 -42n = 42 Divide each side by '-42'. n = -1 Simplifying n = -1
| -13-p=-11 | | y=4865x+56743 | | (2x-4)/7=-6x | | y=4865x+1996559th | | b/16=4 | | 11t+4(1-4t)= | | 27=16+n | | 4t-10/5 | | 3n+8=5(n-5)+6 | | b+-17=-31 | | -9*5-4Y=36 | | x^2-2dx-y^2=0 | | 15=n/2 | | -9*3-4Y=36 | | (5x-2)/(5x+2)=(x+2)/(x+4) | | 6(x+2)+20x-4=8(x-2)+8 | | 3*2-6Y=-18 | | 3*4-6Y=-18 | | 0.4x-0.7x-20=1 | | 16(1/2x)^4 | | 5(2m+1)=4m+12 | | (1-8/9)/((1/5)/9+2/9) | | 5x^2-10=2x^2 | | -5(y+6)=-10 | | 28=x+9 | | -45.00+15.00=15 | | 30=4x | | 3x^2-1=10 | | (1/5)/9+2/9 | | tn=4n-4 | | 32=-2a | | (x+3)/(2) |